TINJAUAN YURIDIS HAK DAN KEWAJIBAN PASIEN SEBAGAI KONSUMEN DALAM PELAYANAN MEDIS - Anggraeni Endah Kusumaningrum (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2014)
Health as one of the basic human needs in addition of food, clothing and shelter. Human life becomes meaningless if sick, because the sick people may not be able to perform daily activities well. Therefore any persons who are ill or patients require definitive treatment and care physicians to be healthy again.The relationship between doctors and patients raise a therapeutic transaction i.e. a transaction or agreement to determine therapy or provide healing services.Through therapeutic transaction then there are rights and obligations for both of them to be protected. As stipulated in ActNo. 8 of 1999 on Consumer Protection, Act No. 36 of 2009 on Health and Act No. 29 of 2004 on the Practice of Medicine.